DIGITAL TAXATION: BALANCING INNOVATION AND REGULATION (International scientific-electronic journal “Pioneering studies and theories”, 2025)
The rapid expansion of the digital economy has transformed global trade, raising complex taxation challenges. As businesses increasingly operate across borders through digital platforms, traditional tax frameworks struggle to adapt. This study examines the evolving landscape of digital taxation, focusing on the delicate balance between fostering innovation and ensuring effective regulation. Key issues include profit shifting, tax avoidance, and jurisdictional conflicts, which complicate fair taxation in a globalized digital market.Governments worldwide are implementing digital services taxes (DSTs) and advocating for global tax reforms, such as the OECD’s Two-Pillar Solution, to address these challenges. However, concerns persist regarding the impact on startups, technological growth, and investment incentives. Striking the right balance requires policies that prevent tax base erosion while maintaining a competitive environment for digital enterprises.This paper explores existing digital tax frameworks, their economic implications, and potential policy solutions. It highlights the need for international cooperation to create a fair and sustainable taxation system that adapts to evolving business models without stifling technological progress. The findings contribute to the ongoing debate on shaping a taxation model that promotes both innovation and regulatory compliance in the digital economy